GREEN MARKETING: A SUSTAINABLE BUSINESS STRATEGY IN THE ECO-CONSCIOUS ERA - Siti Asiyah; M. Khoirul Anwarodin Brotosuharto; Firda Fadri (EKUITAS (Jurnal Ekonomi dan Keuangan), 2025)
This research examines the role of green marketing in mediating between green knowledge and CSR on green trust. It investigates the correlation among four key concepts: green trust, green knowledge, CSR, and green marketing. An empirical survey tested the proposed hypotheses. Data were collected from 119 respondents in East Java, Indonesia, who consume Le Minerale bottled drinking water. Structural Equation Modeling using Partial Least Squares (SEM-PLS) was used to assess the research model. Results reveal that all direct relationships are positive and significant. Specifically, the analysis found green marketing does not significantly mediate the relationship between green knowledge and green trust. This means green knowledge does not increase green trust through green marketing. However, the indirect effect of CSR on green trust via green marketing is significant. This highlights that CSR builds green trust when green marketing is a mediator. These results suggest that green marketing can be an effective strategy for building consumer green trust. The research finds that green marketing helps companies enhance their consumers’ green trust. By exploring the roles of green knowledge and CSR in green trust through green marketing, this research highlights the value of honest and effective strategies. It also offers managerial implications for sustainable marketing.